Genetic alterations in gliosarcoma and giant cell glioblastoma - Oh, Ji Eun; Ohta, Takashi; Nonoguchi, Naosuke; Satomi, Kaishi; Capper, David; Pierscianek, Daniela; Sure, Ulrich; Vital, Anne; Paulus, Werner; Mittelbronn, Michel; Antonelli, Manila; Kleihues, Paul; et al. (Brain pathology, 2015)
The majority of glioblastomas develop rapidly with a short clinical history (primary glioblastoma IDH wild-type), whereas secondary glioblastomas progress from diffuse astrocytoma or anaplastic astrocytoma. IDH mutations are the genetic hallmark of secondary glioblastomas. Gliosarcomas and giant cell glioblastomas are rare histological glioblastoma variants, which usually develop rapidly. We determined the genetic patterns of 36 gliosarcomas and 19 giant cell glioblastomas. IDH1 and IDH2 mutations were absent in all 36 gliosarcomas and in 18 of 19 giant cell glioblastomas analyzed, indicating that they are histological variants of primary glioblastoma. Furthermore, LOH 10q (88%) and TERT promoter mutations (83%) were frequent in gliosarcomas. Copy number profiling using the 450k methylome array in 5 gliosarcomas revealed CDKN2A homozygous deletion (3 cases), trisomy chromosome 7 (2 cases), and monosomy chromosome 10 (2 cases). Giant cell glioblastomas had LOH 10q in 50% and LOH 19q in 42% of cases. ATRX loss was detected immunohistochemically in 19% of giant cell glioblastomas, but absent in 17 gliosarcomas. These and previous results suggest that gliosarcomas are a variant of, and genetically similar to, primary glioblastomas, except for a lack of EGFR amplification, while giant cell glioblastoma occupies a hybrid position between primary and secondary glioblastomas.
Gesehen am 22.06.2020